Neonatologists’ Resuscitation Decisions at Birth for Extremely Premature Infants. A Belgian Qualitative Study - Cavolo, Alice; Dierckx de Casterlé, Bernadette; Naulaers, Gunnar; Gastmans, Chris (Frontiers in Pediatrics, 2022)
Objective. Deciding whether initiating or withholding resuscitation at birth for extremely preterm infants (EPIs) can be difficult due to uncertainty on outcomes. Clinical uncertainty generates ethical uncertainty. Thus, physicians’ attitudes and perspectives on resuscitation of EPIs might influence (non)resuscitation decisions. We aimed at understanding how neonatologists make clinical-ethical decisions for EPI resuscitation and how they perceive these decisions. Method. We performed a nationwide qualitative study using a constructivist account of grounded theory. Face-to-face, semi-structured in-depth interviews with neonatologists comprised data collection. For data analysis, we used the Qualitative Analysis Guide of Leuven. Results. We interviewed 20 neonatologists working in 10 hospitals in Belgium. Participants’ decision-making can be described as consensus-based, gestational age-based, contextualized, progressive, and shared. All participants agreed on the importance of using the consensus expressed in guidelines as a guidance for the decision-making (consensus-based). Consequently, all 20 participants use GA thresholds indicated in the guidelines (GA-based). However, they use these thresholds differently in their decisions. Few participants rigidly follow established thresholds. The vast majority reported using additional contextual factors (eg, birthweight or parents’ wishes) in the decision-making, rather than only the EPIs’ GA (contextualized). All participants agreed on the importance of involving the parents in the decision-making (shared), and indeed parents’ wishes were among the most valued factors considered in the decision-making. However, the extent to which parents were involved in the decision-making depended on the infant’s GA. Participants identified a grey zone (23-24 weeks) in which parents’ were viewed as the main decision-makers due to the high clinical uncertainty. This mean that participants tend to follow parents’ request even when they disagree with it. Outside the gray zone, physicians were viewed as the main decision-makers. This mean that, although parents’ wishes were still considered, counselling was more directive and the final decision was made by the physician. Conclusions. Although an EPI’s GA remains the main factor guiding neonatologists’ (non)resuscitation decisions, other factors are seriously considered in the decision-making process. All neonatologist participants agreed on the importance of involving parents in the decision-making. However, they involve parents differently depending on the EPI’s GA.